Duty calls Dunkirk - Holland, James 1970- (Puffin, 2011)
Friday 24 May, 1940. Private Johnny Hawke, aged sixteen, awakens to artillery fire. Hours later, stukas scream down from the sky. Messerschmitt fighters roar towards them. Trucks burst into flames. Now men and mules lay dead and dying, severed limbs twisted grotesquely as blood soaks into the cobbled streets. Young Private Hawke just wants to do his duty and serve his country. But as he - and his fellow soldiers - prepare to stop the German advance, there's only one question on everyone's lips... How will they survive?